Simplify: \dfrac{1}{1- \sqrt{x}} - \dfrac{1}{1+ \sqrt{x}} + \dfrac{\sqrt{x}}{1 - x}
Solution:
= \dfrac{1}{1 - \sqrt{x}} - \dfrac{1}{1 + \sqrt{x}} + \dfrac{\sqrt{x}}{1 - x}
= \dfrac{1(1 + \sqrt{x}) - 1(1 - \sqrt{x})}{(1+\sqrt{x})(1 - \sqrt{x})} + \dfrac{\sqrt{x}}{1 - x}
= \dfrac{1 + \sqrt{x} - 1 + \sqrt{x}}{1^2 - ( \sqrt{x})^2} + \dfrac{\sqrt{x}}{1 - x}
= \dfrac{2 \sqrt{x}}{1 - x} + \dfrac{ \sqrt{x}}{1 - x}
= \dfrac{2\sqrt{x} + \sqrt{x}}{1 -x}
= \dfrac{3 \sqrt{x} }{1 - x}
Answer
0 Comments
You can let us know your questions in the comments section as well.